Broken plea : the explosive search for truth behind the Idaho murders - Whitcomb, Christopher, 1959- (Harper Select, 2026)
"In the early morning hours of November 13, 2022, four lives were lost in a brutal crime in Moscow, Idaho?and a nation demanded answers. When a suspect accepted a plea bargain, the story seemed settled. Justice, many believed, had been served. Broken Plea challenges that assumption. Drawing on court records, investigative timelines, witness statements, and apparently overlooked inconsistencies, this meticulously researched exposé examines how a rush to judgment may have shaped one of the most closely watched murder cases in recent memory. As the official narrative hardened, critical leads went unexplored, contradictory evidence was minimized, and alternative explanations faded from view. This book does not claim certainty where none exists. Instead, it asks the questions that were never fully pursued: What happens when pressure to close a case outweighs the search for truth? What evidence may have been sidelined, and why? And what are the consequences when a plea doesn't end scrutiny but invites it? Clear-eyed, unsparing, and deeply unsettling, Broken Plea reopens the case--and invites readers to look again at what justice demands when the truth remains unresolved."--